Symptomatic bone marrow metastases in breast cancer: A retrospective cohort study - Yang, Ruohan; Jia, Lin; Lu, Guanyu; Lv, Zheng; Cui, Jiuwei (Frontiers in Oncology, 2022)
Objective Breast cancer symptomatic bone marrow metastasis (BMM) is rare and has a poor prognosis. Chemotherapy is usually the primary treatment, but it has limited efficacy, resulting in dose reduction and a decrease in quality of life due to the adverse effects of the agent. Other than chemotherapy, there are no other treatment studies for BMM. This study aimed to explore the clinicopathological characteristics of BMM patients with breast cancer, the prognosis using different treatment modalities, and the risk factors that affect the prognosis. Methods This retrospective study included patients diagnosed with breast cancer BMM from January 2018 to January 2022 in the Cancer Center of the First Hospital of Jilin University. The analysis focused on the characteristics of the patients, the treatment regimen, and the prognosis. Results Of 733 patients with advanced breast cancer, 33 patients were identified with BMM. All patients showed a hemoglobin decrease, and 25 (75.75%) presented with a fever of unknown origin. As for the metastasis breast cancer subtype, 25 (75.75%) were hormone receptor (HR) positive/human epidermal growth factor receptor 2 (HER2) negative, three (9.09%) had HER2 overexpression, and five (15.15%) were triple negative. The BMM patients had a median progression-free survival (PFS) of 7 months (1–21 months) and a median overall survival (OS) of 18 months (2–108 months). Among 25 HR+/HER2− BMM patients treated with different modalities, the median OS of the endocrine therapy (ET) group was 23 months, compared with 5 months in the chemotherapy group. Cox proportional hazards models suggested that higher Eastern Cooperative Oncology Group (ECOG) scores and old age were associated with shorter survival. Conclusion When breast cancer patients present with anemia and fever of unknown origin, BMM should be considered. For HR+/HER2− patients with good physical status and can receive active treatment, CDK4/6 inhibitors combined with ET can be used to control disease progression, improve quality of life, and prolong survival.